Japanese Migration Patterns to Mexico: Settler Colonialism and Corporate Mobility - Alejandro Mendez Rodriguez (Genealogy, 2024)
This article describes two distinct periods in the migratory flow of the Japanese to Mexico under the framework of settler colonialism. A historical review revealed that some agriculture colonies were formed by the Japanese in the south of Mexico with the goal to settle those lands. This was possible thanks to inter-governmental agreements in the early 1900s. Recently, the migration flow of the Japanese to Mexico is due to corporate mobility, mainly in the Bajío region in Mexico where many Japanese automakers are located. The implications of both types of immigration in both regions are described as part of this research. This research contributes to the understanding of migration flows and mobility patterns of the Japanese in Mexico.